Konstruksi Relasi Kuasa dalam Delik Inses Persetubuhan terhadap Anak oleh Orang Tua Kandung - Laila Hayati; Nurunnisa Nurunnisa (AHKAM, 2026)
Although the offense of sexual intercourse with a child has been regulated in Indonesian criminal law, its legal construction has not explicitly positioned the power relations between parents and children as a constitutive element of the offense, so the specific characteristics of incest crimes have not been fully reflected in legal protection for victims. This study aims to analyze the construction of power relations in the incest offense of sexual intercourse with a child by biological parents and to examine sustainable legal protection for child victims of incest. This study used normative legal research with statutory, conceptual, and case approaches. Legal materials were obtained through library research on legislation, legal literature, and court decisions related to incest crimes. The results show that the Child Protection Law, the Law on Sexual Violence Crimes, and the 2023 Criminal Code still position power relations as circumstances that aggravate punishment rather than as an essential element of the offense. In fact, power relations constitute the main factor that enables domination, manipulation, and nonphysical coercion of children in incest crimes. In addition, legal protection for victims still tends to be oriented toward punishing perpetrators and has not fully prioritized comprehensive and sustainable victim recovery. These findings contribute to the development of studies on juvenile criminal law, particularly in reconstructing incest offenses based on power relations and victim protection. The conclusion of this study affirms that power relations need to be positioned as a constitutive element in incest offenses so that criminal law can more substantively represent the characteristics of the crime. The implications of this study indicate the need for criminal law reform that is more responsive to child protection by strengthening a substantive justice approach and sustainable victim recovery.